Mt. Lykaion Excavation and Survey Project - University of Pennsylvania - Museum of Archaeology and Anthropology; University of Arizona; The American School of Classical Studies at Athens (2009)
[Dt.:] Die Seite informiert ausführlich über das griechisch-amerikanische Grabungsprojekt im Lykaion-Gebirge. Neben Grabungsberichten, Plänen und Fotos finden sich auch die wichtigsten schriftlichen Quellen, frühe Reiseberichte, eine Bibliographie und interessante Links zum Thema. - [Engl.:] The site informs in detail on the Greek-American excavation project on the Mount Lykaion / Peloponnese. Next to excavation reports, plans and images there is a list of the most important ancient textsources, examples for travel writing, a bibliography, and interesting links on the subject.